2017
DOI: 10.1007/s11325-017-1502-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep habits, fatigue, and sleepiness in Chiclayo-Peru’s bus drivers

Abstract: Fatigue, sleepiness, and a history of accident or near accident were frequent. Having had an accident or near accident was significantly associated with nodding while driving and the number of years as a driver in Chiclayo's bus drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(14 reference statements)
2
9
0
4
Order By: Relevance
“…Según la Escala de Somnolencia de Epworth, aproximadamente la quinta parte de los conductores presentaron somnolencia diurna, y de ellos más de la mitad laboraban en el sistema de rotación 2 x 1. Resultados similares fueron obtenidos en los estudios de Catarino et al (12) y de Guevara & Torres (13) , quienes identificaron que menos de la cuarta parte de los conductores de taxis presentaban somnolencia excesiva diurna, mientras que resultados casi similares fueron hallados por Deza et al (14) quienes evidenciaron que la cuarta parte de los conductores de transporte interprovincial presentaron somnolencia diurna según la misma escala. Asimismo, Suarez Molina (15) y Caso et al (16) hallaron que más de la cuarta parte de los conductores presentaban somnolencia diurna.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Según la Escala de Somnolencia de Epworth, aproximadamente la quinta parte de los conductores presentaron somnolencia diurna, y de ellos más de la mitad laboraban en el sistema de rotación 2 x 1. Resultados similares fueron obtenidos en los estudios de Catarino et al (12) y de Guevara & Torres (13) , quienes identificaron que menos de la cuarta parte de los conductores de taxis presentaban somnolencia excesiva diurna, mientras que resultados casi similares fueron hallados por Deza et al (14) quienes evidenciaron que la cuarta parte de los conductores de transporte interprovincial presentaron somnolencia diurna según la misma escala. Asimismo, Suarez Molina (15) y Caso et al (16) hallaron que más de la cuarta parte de los conductores presentaban somnolencia diurna.…”
Section: Discussionunclassified
“…Las características sociodemográficas de los participantes de los diversos estudios relacionados con la presente investigación no pueden ser contrastadas, debido a que cada una de las características poblacionales en análisis son propias, solo se mencionarán las características más resaltantes halladas en cada uno de los estudios, por ejemplo, los estudios de Anund et al (20) , Muñoz Escobar (17) , Deza et al (14) , Intriago Alvarez (19) y Suarez Molina (15) concuerdan en que la mayoría de los conductores que participaron en cada uno de los estudios presentaban sobrepeso u obesidad. Al respecto, se puede mencionar que estos problemas nutricionales, podría deberse al sedentarismo que los conductores experimentan durante toda su actividad laboral, sin opción de realizar algún tipo de ejercicio físico, puesto que esta actividad demanda de una gran concentración por parte del conductor.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There are multiple reports that show high levels of sleepiness, long hours, and insufficient sleep among professional drivers in this region in both countries with and without provisions. [11][12][13][14][15][16] For example, one study from Argentina showed that drivers on average drove almost 16 hours (4 hours above the limit). 11 Similarly, studies from Brazil have shown average driving hours that exceed the limits imposed by law, as well as high prevalence of sleepiness and use of amphetamines.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue, sleepiness, excessive speed, use of mobile phones, lapses, errors, and traffic violations were related to injuries from motor vehicle crashes among bus drivers in Turkey13 ) . Nearly three quarters (74%) of bus drivers in Peru reported that while driving they experienced fatigue, 25% felt sleepy, and “nodding off” and these increase the risk of accidents or near accidents14 ) . In Thailand, 73.4% of bus drivers reported drowsy driving; although this study did not investigate associated accidents15 ) .…”
Section: Introductionmentioning
confidence: 99%